2013
DOI: 10.1210/en.2012-1797
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Surfactant Protein A (SP-A) and SP-D or in TLR2 Manifest Delayed Parturition and Decreased Expression of Inflammatory and Contractile Genes

Abstract: Previously we obtained compelling evidence that the fetus provides a critical signal for the initiation of term labor through developmental induction of surfactant protein (SP)-A expression by the fetal lung and secretion into amniotic fluid (AF). We proposed that interactions of AF macrophage (Mϕ) Toll-like receptors (TLRs) with SP-A, at term, or bacterial components, at preterm, result in their activation and migration to the pregnant uterus. Herein the timing of labor in wild-type (WT) C57BL/6 mice was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 82 publications
0
90
0
Order By: Relevance
“…The majority of the pregnant mice (~84%) delivered 1 to 2 days late or had to be sacrificed at 22.5 dpc because of a failure to deliver spontaneously ( Figure 1A). Thus, a pronounced and statistically significant delay in the time to parturition was observed in SRC-1/-2 dhet females bred to genotypically matched (6,15). To determine whether a deficiency of SRC-1/-2 affected the activation of inflammatory signaling pathways, the proinflammatory transcription factors, NF-κB p65 and p50, were analyzed in myometrial cytoplasmic and nuclear fractions by immunoblotting.…”
Section: Src-1/src-2 Double Deficiency In Mice Results In Delayed Labormentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the pregnant mice (~84%) delivered 1 to 2 days late or had to be sacrificed at 22.5 dpc because of a failure to deliver spontaneously ( Figure 1A). Thus, a pronounced and statistically significant delay in the time to parturition was observed in SRC-1/-2 dhet females bred to genotypically matched (6,15). To determine whether a deficiency of SRC-1/-2 affected the activation of inflammatory signaling pathways, the proinflammatory transcription factors, NF-κB p65 and p50, were analyzed in myometrial cytoplasmic and nuclear fractions by immunoblotting.…”
Section: Src-1/src-2 Double Deficiency In Mice Results In Delayed Labormentioning
confidence: 99%
“…Near term, increased uterine stretch (12,13) and factors produced by the developing fetus (6,(14)(15)(16) may provide inflammatory stimuli. Previously, we (6) and others (17) suggested that the fetus may provide a signal via pulmonary surfactant, a developmentally regulated, glycerophospholipid-rich lipoprotein produced by pulmonary alveolar type II cells and secreted into AF in increased amounts during late gestation (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mendelson group further demonstrated that SP-A promotes parturition by shuttling amniotic fluid macrophages to the myometrium and increasing uterine IL-1β levels. A subsequent study reported that parturition is delayed by an average of 12 hours in the second pregnancies of SP-A-deficient mice (12). However, as both mother and fetuses lacked SP-A, these experiments did not reveal whether fetal SP-A is indeed a signal for parturition.…”
Section: Does the Fetus Have A Say In Gestational Length?mentioning
confidence: 87%
“…Importantly, fetal SRC-1/-2 deficiency led to longer delays in parturition than loss of SP-A alone, indicating that SRC-1 and SRC-2 have other targets that regulate the onset of parturition (12). Because mice completely lacking SRC-1 or SRC-2 die at birth due to respiratory distress and alveolar collapse, Gao and colleagues examined expression of enzymes that catalyze metabolic reactions required for lung development and found that expression of lysophosphatidylcholine acyl transferase 1 (LPCAT1), an enzyme that is responsible for synthesis of surfactant phospho- Figure 1.…”
Section: Remaining Questions and Future Directionsmentioning
confidence: 99%